Effect of yoga exercises on lung volumes, vital capacity, and attention span in school going students - Reema Joshi; Manisha Rathi; Komal Preet Kaur (Physiotherapy Quarterly)
Objective The digital age has made children more dependent on digital sources for study and entertainment, which leads to increased physical inactivity that contributes to reduced work breathing and attention. Yoga Sana can be a promising form of physical activity that improves a child’s lung function and attention span if, started at a young age. To find out the effect of yoga exercises on lung volumes, vital capacity, and attention span in school-going children.